TNF-Signaling Modulates Neutrophil-Mediated Immunity at the Feto-Maternal Interface During LPS-Induced Intrauterine Inflammation - Presicce, Pietro; Cappelletti, Monica; Senthamaraikannan, Paranthaman; Ma, Feiyang; Morselli, Marco; Jackson, Courtney M.; Mukherjee, Shibabrata; Miller, Lisa A.; Pellegrini, Matteo; Jobe, Alan H.; Chougnet, Claire A.; Kallapur, Suhas G. (Frontiers in Immunology, 2020)
Accumulation of activated neutrophils at the feto-maternal interface is a defining hallmark of intrauterine inflammation (IUI) that might trigger an excessive immune response during pregnancy. Mechanisms responsible of this massive neutrophil recruitment are poorly investigated. We have previously showed that intraamniotic injection of LPS in rhesus macaques induced a neutrophil predominant inflammatory response similar to that seen in human IUI. Here, we demonstrate that anti-TNF antibody (Adalimumab) inhibited ~80% of genes induced by LPS involved in inflammatory signaling and innate immunity in chorio-decidua neutrophils. Consistent with the gene expression data, TNF-blockade decreased LPS-induced neutrophil accumulation and activation at the feto-maternal interface. We also observed a reduction in IL-6 and other pro-inflammatory cytokines but not prostaglandins concentrations in the amniotic fluid. Moreover, TNF-blockade decreased mRNA expression of inflammatory cytokines in the chorio-decidua but not in the uterus, suggesting that inhibition of TNF-signaling decreased the inflammation in a tissue-specific manner within the uterine compartment. Taken together, our results demonstrate a predominant role for TNF-signaling in modulating the neutrophilic infiltration at the feto-maternal interface during IUI and suggest that blockade of TNF-signaling could be considered as a therapeutic approach for IUI, the major leading cause of preterm birth.